A formação do professor de Matemática e a utilização de recursos digitais: uma proposta inspirada no contexto da pandemia da COVID-19 - Senna, Karina Aguena Shimizu (2024)
This study presents and discusses the results of a research aimed at analyzing the implications of training for mathematics teachers in face-to-face classes using digital technologies in the period after social isolation. The qualitative research, carried out with seven mathematics teachers from public schools who taught in the final years of elementary school, was based on the training of mathematics teachers in the use of new technologies and the possible contributions of this practice to classroom teaching. For the development of the research, the training was divided into two modules, the first was developed through two workshops that covered the main features of Google Tools and the second was developed through four workshops that presented the main features of the 2D visualization window of the GeoGebra software and how to associate the use of this application with the skills developed in the Currículo em Ação material. For data collection, in addition to the recordings made during the workshops, a questionnaire was made available before the start of the training to guide the paths and strategies to be developed in the workshops, a questionnaire at the end of each module to analyze each theme, Google Tools and GeoGebra, and another at the end related to the Training Course. According to the bibliographic study carried out, the integration of digital technologies in teaching has been discussed for some time, but since the period during remote teaching, the subject has once again come to the fore, as teachers suddenly had to use digital resources to continue teaching. But despite the importance of the subject, technological integration and teacher training in school institutions were still insufficient. For the literature review, a survey was carried out of productions available in national journals classified in Qualis CAPES, 2017 - 2020, categorized as A1, A2, A3, B1 and B2. Kenski, Borba, Penteado, Scucuglia, Gadanidis and Richit were used for the theoretical basis. For data analysis, the study was based on the observation of qualitative data and maintaining this conjunction, the quantitative interpretation was not excluded, since they served as a foundation and authenticity for the qualitative point of view. Therefore, the research showed that the training enabled the teachers to use technological resources safely, enabled the participants to take ownership of the basic concepts, helped in the development of teaching practices, led to reflection on teaching methodologies, allowed the sharing of experiences between peers and made it possible to associate technological resources with the curriculum. As a result, the combination of these actions provides an opportunity for qualitative and meaningful teaching, always seeking the role of the student so that they can develop their own knowledge. In addition to the implications found, the study can help teachers who teach mathematics, teacher training programs and undergraduate students in mathematics or related areas. In addition, this material can be used as inspiration for extension courses on initial or continuing training for mathematics teachers.